2017
DOI: 10.22192/ijcrcps.2017.04.01.001
|View full text |Cite
|
Sign up to set email alerts
|

The Flavonoids Ameliorates: Protective Mechanisms in Neurodegenerative Diseases

Abstract: Flavonids exhibits various neuroprotective actions. They have a potential to protect neurons against injury induced by neurot oxins in brain. Flavonoids also suppress neuro-inflammation and promote memory, learning and cognitive function. Oxidative stress is the well accepted concept in the etiology and progression of neurodegenerative diseases. Thus the therapeutic agent is targeted against suppressing and alleviating the oxidative stress-induced cellular damage. Flavonoids are reported to possess neuroprotec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Body weight change is regarded as an indicator of toxicity in chronic toxic agent exposure. [ 37 ] Several studies demonstrated the relation between lung injury and an increase in the pulmonary index. [ 8,38 ] In the current study, PQ effectively decreased body weight gain and increased pulmonary index in rats, which is in line with findings reported by Pourgholamhossein et al [ 39 ] Furthermore, the administration of CGA can effectively prevent weight changes caused by PQ toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Body weight change is regarded as an indicator of toxicity in chronic toxic agent exposure. [ 37 ] Several studies demonstrated the relation between lung injury and an increase in the pulmonary index. [ 8,38 ] In the current study, PQ effectively decreased body weight gain and increased pulmonary index in rats, which is in line with findings reported by Pourgholamhossein et al [ 39 ] Furthermore, the administration of CGA can effectively prevent weight changes caused by PQ toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The word of lichen planus is derived from the Greek word "leichen" means tree moss and Latin word "planus" means flat 6 . Lichen planus is a chronic T-cell mediated autoimmune disease, which affects the oral mucosa, skin, genital mucosa, scalp, and nails 7 .…”
Section: Discussionmentioning
confidence: 99%
“…One of the major fatty acid in P. tricornutum is the ω-3 fatty acid EPA (C20:5), having a significant commercial importance in pharmaceutical and nutraceutical industries [9,10] . These long chain polyunsaturated fatty acids (LC-PUFAs) have a bioactive role against a variety of disorders, including coronary heart disease, thrombosis, and recently in prospective adjuvant therapy in COVID-19-related cardiovascular problems [11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%